79.2k views
0 votes
Use a right triangle to write the following expression as an algebraic expression. Assume that x is positive and that the given inverse trigonometric function is defined for the expression in x. sin (cos^-1 14x) Show the triangle that is correct to write the given expression as an algebraic expression?

1 Answer

3 votes

Answer:


Sin(Cos^(-1) (14x))=√(1-196x^2)

Step-by-step explandation:

First of all, from the figure we can define the cosine and sine functions as


Cos(theta)=(adjacent )/(hypotenuse )


Sin(theta)=(Opposite)/(hypotenuse )

And by analogy with the statement:


14x=(adjacent )/(hypotenuse )

Which can be rewritten as:


(14x)/(1)=(adjacent )/(hypotenuse )

You have then that, for the given triangle, the values of the adjacent and hypotenuse sides, are then given by:

:

Adjacent=14x

Hypotenuse=1

And according to the Pythagorean theorem:


Opposite=√(1-(14x)^2)

Finally, by doing:


Cos^-1(14x)=theta

We have that:


Sin(Cos^(-1) (14x))=Sen(theta)=(Opposite)/(hypotenuse)=(√(1-(14x)^2))/(1)=√(1-(14x)^2)

Use a right triangle to write the following expression as an algebraic expression-example-1
User JeffSahol
by
4.2k points